2006
DOI: 10.1196/annals.1378.067
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Appendage Transcriptional Profile in Patients with Atrial Fibrillation with Structural Heart Diseases

Abstract: During the last few years DNA microarray studies of gene expression changes in human atrial tissues from patients with and without atrial fibrillation (AF) have been performed. For this purpose, tissue samples are usually collected from AF patients undergoing open heart surgery. These investigations have limitations associated with the unavoidable heterogeneity of compared groups which is due to the presence of various structural changes accompanying different sets of underlying heart diseases in both groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
(41 reference statements)
0
10
0
1
Order By: Relevance
“…Several genes, including those for ion channels, are known to be involved in the pathogenesis of atrial fibrillation. 63 Barth et al found that the gene expression profile of the fibrillating atrial myocardium has a ventricular-like pattern. 64 These findings imply that ion channels may represent novel therapeutic targets for cardiac arrhythmia and HF.…”
Section: Chamber-specific Gene Expressionmentioning
confidence: 99%
“…Several genes, including those for ion channels, are known to be involved in the pathogenesis of atrial fibrillation. 63 Barth et al found that the gene expression profile of the fibrillating atrial myocardium has a ventricular-like pattern. 64 These findings imply that ion channels may represent novel therapeutic targets for cardiac arrhythmia and HF.…”
Section: Chamber-specific Gene Expressionmentioning
confidence: 99%
“…CSDA is a member of the protein family containing the highly conserved coldshock domain and are considered as transcriptional and translational regulators (30,31). As such, it is perceivable that the increase in CSDA–PP1c association may underlie some of the transcriptional changes observed in PAF and perhaps drive the eventual electrical and structural remodeling in chronic AF (32,33). However, other than one study showing by Northern blot that CSDA is highly expressed in cardiac muscles (34), its role in the heart is completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Genes correlating with AF belonged to different functional categories, including sarcomere organization, contraction, Ca 2+ homeostasis, signaling and transcription regulation, extracellular matrix (ECM) interactions, and oxidative stress. Downregulation of MT1/2 and ALDH2 , known protectors against oxidative stress, may contribute to oxidative stress maintenance in myocardial tissues of AF patients . In another analysis performed in 2006 by Kharlap et al 39 genes were differentially expressed in pathologically altered tissue samples independently of underlying structural heart disease type.…”
Section: The Use Of Microarrays In the Diagnosis Of Arrhythmiasmentioning
confidence: 97%
“…Downregulation of MT1/2 and ALDH2 , known protectors against oxidative stress, may contribute to oxidative stress maintenance in myocardial tissues of AF patients . In another analysis performed in 2006 by Kharlap et al 39 genes were differentially expressed in pathologically altered tissue samples independently of underlying structural heart disease type. Significant genes were associated with cell proliferation, regulation of transcription, apoptosis, and signal transduction.…”
Section: The Use Of Microarrays In the Diagnosis Of Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation